Sound-Action Symbolism - Vainio, Lari; Vainio, Martti (Frontiers in Psychology, 2021)
Recent evidence has shown linkages between actions and segmental elements of speech. For instance, close-front vowels are sound symbolically associated with the precision grip, and front vowels are associated with forward-directed limb movements. The current review article presents a variety of such sound-action effects and proposes that they compose a category of sound symbolism that is based on grounding a conceptual knowledge of a referent in articulatory and manual action representations. In addition, the article proposes that even some widely known sound symbolism phenomena such as the sound-magnitude symbolism can be based on similar sensorimotor grounding. It is also discussed that meaning of suprasegmental speech elements in many instances is similarly grounded in body actions. Sound symbolism, prosody and body gestures might originate from the same embodied mechanisms that enable a vivid and iconic expression of a meaning of a referent to the recipient.